AFM observation of single membrane proteins and its application to nano biodevices - Kasai, N; Ramanujan, C; Sumitomo, K; Shinozaki, Y; Shimada, A; Ryan, J; Torimitsu, K (2010)
Recent progress on nanotechnology including nanostructure fabrication and nanometer-scale measurement techniques, and work on biomolecules whose size is equivalent to that covered by nanotechnology, are expected to result in the creation of a new research field called nano-bio science. This article introduces our recent work on the observation of single biomolecule; reconstituted a receptor protein into an artificial lipid membrane using an atomic force microscope (AFM). An AFM is a measurement tool that enables us to observe nanometer-scale objects in a liquid environment. We also examine the orientation of the proteins in proteoliposomes with the dynamic light scattering technique (DLS). Most receptor proteins have orientations in molecules, for example the extracellular and intracellular domains. Determining the protein orientation is essential for nano-biodevice fabrication if we wish to utilize the protein's function. We also introduce our recent attempt to realize a nano-bio device; a very small device obtaining and utilizing biological functions; using our state-of-the-art nanofabrication technique and a technique for handling receptor proteins. Thus, by combining nanotechnology and biotechnology to realize nano-biodevices, we can produce ultra-small biological sensors for implantation. Further improvements are expected. © 2010 The Institute of Electrical Engineers of Japan.